2009
DOI: 10.1086/605413
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoantigen‐Expanded Human γδ T Cells Display Potent Cytotoxicity against Monocyte‐Derived Macrophages Infected with Human and Avian Influenza Viruses

Abstract: Our findings suggest a potentially novel therapeutic approach to seasonal, zoonotic avian, and pandemic influenza-the use of phosphoantigens to activate gammadelta T cells against influenza virus infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
154
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 125 publications
(160 citation statements)
references
References 49 publications
6
154
0
Order By: Relevance
“…The following anti-human monoclonal antibodies (MAbs) were used in this study: anti-HLA-A2 (BB7.2), anti-CD45RO (UCHL1), anti-CCR7 (3D12), anti-CD62L (DREG-56), anti-IFN-␥ (25723.11), anti-TNF-␣ (6401.1111), antiperforin (G9), anti-granzyme B (GB11), and antiCD107a (H4A3) (all from BD Biosciences) and anti-CD3 (HIT3a), anti-CD8 (HIT8a), anti-CD19 (HIB19), anti-CCR5 (HEK/1/85a), and anti-CXCR3 (TG1/ CXCR3) (all from BioLegend). For intracellular staining, cells were fixed, permeabilized, and then labeled with the indicated antibody as we described before (36,44,59). In order to examine tetramer staining, cells were incubated with anti-CD3, anti-CD8, and HLA-A2/M1 [58][59][60][61][62][63][64][65][66] tetramer (Beckman Coulter, CA) for 30 min and then analyzed by flow cytometry.…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following anti-human monoclonal antibodies (MAbs) were used in this study: anti-HLA-A2 (BB7.2), anti-CD45RO (UCHL1), anti-CCR7 (3D12), anti-CD62L (DREG-56), anti-IFN-␥ (25723.11), anti-TNF-␣ (6401.1111), antiperforin (G9), anti-granzyme B (GB11), and antiCD107a (H4A3) (all from BD Biosciences) and anti-CD3 (HIT3a), anti-CD8 (HIT8a), anti-CD19 (HIB19), anti-CCR5 (HEK/1/85a), and anti-CXCR3 (TG1/ CXCR3) (all from BioLegend). For intracellular staining, cells were fixed, permeabilized, and then labeled with the indicated antibody as we described before (36,44,59). In order to examine tetramer staining, cells were incubated with anti-CD3, anti-CD8, and HLA-A2/M1 [58][59][60][61][62][63][64][65][66] tetramer (Beckman Coulter, CA) for 30 min and then analyzed by flow cytometry.…”
Section: Cellsmentioning
confidence: 99%
“…After 1 h, the cells were washed and then cocultured with influenza virus bulk CTLs or M1 [58][59][60][61][62][63][64][65][66] -specific CTLs at the indicated E/T ratio for 4 to 6 h. After incubation, total cells were stained with anti-CD3 and EthD-2 as we described before (44). Dead target cells were identified as EthD-2-positive cells out of CD3-negative cells, and cell death was analyzed by flow cytometry.…”
Section: Cellsmentioning
confidence: 99%
“…23 Briefly, CD40-B cells were labeled with 3,39-dioctadecyloxacarbocyanine perchlorate before beginning coculture. Cells were harvested and stained with propidium iodide for 15 min and analyzed by flow cytometry at the indicated times during coculture.…”
Section: Cell Death Assaymentioning
confidence: 99%
“…23,24 Similarly to the contribution of murine cd-T cells during recovery after influenza-caused pneumonia, 25 the beneficial effects of human Vc9Vd2 cd-T cells against influenza virus infection have also recently been confirmed by our laboratory. 22,26,27 Through the direct killing of virus-infected cells and the production of antiviral cytokines, Vc9Vd2 cd-T cells can control infection by different strains of the influenza virus, such as human seasonal H1N1, pandemic H1N1, and the avian H5N1 and H9N2 viruses. 22,26,27 Moreover, these antiviral activities can be significantly improved by phosphoantigen stimulation, which confers sufficient protection on humanized mice to prevent lethal influenza virus infection.…”
Section: Involvement Of Cd-t Cells In Infectious Diseasesmentioning
confidence: 99%
“…22,26,27 Through the direct killing of virus-infected cells and the production of antiviral cytokines, Vc9Vd2 cd-T cells can control infection by different strains of the influenza virus, such as human seasonal H1N1, pandemic H1N1, and the avian H5N1 and H9N2 viruses. 22,26,27 Moreover, these antiviral activities can be significantly improved by phosphoantigen stimulation, which confers sufficient protection on humanized mice to prevent lethal influenza virus infection. 28 In addition, another group has shown that cd-T cells can initiate efficient adaptive immunity through processing and presenting influenza virus-derived peptides to CD4 1 and CD8 1 T cells.…”
Section: Involvement Of Cd-t Cells In Infectious Diseasesmentioning
confidence: 99%